Pengembangan Media Pembelajaran PowerPoint Interaktif pada Pokok Bahasan Statistika Kelas X di SMA Negeri 3 Kota Pasuruan - Wildan Mubahzah; Maya Rayungsari; Keto Susanto (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
The mathematics learning process at high school level often faces challenges in terms of difficulties in understanding concepts. Conventional learning media is not interesting and interactive enough so it is less effective in understanding the material. This research aims to produce learning media using PowerPoint on the subject of statistics for class X. The development model used is the R&D model with the ADDIE development pattern, which consists of five stages: analysis, design, development, implementation and evaluation. The data collection technique used was a questionnaire. Data collection instrument that will obtain quantitative and qualitative data. Qualitative data was obtained from suggestions and input, while quantitative data was obtained from questionnaire calculations. The data analysis technique used is validation data analysis and learning media practicality data. The results of research validation analysis by three validators, namely media experts, material experts and learning experts using a Likert scale, show that the average validation of learning media is in the very feasible category. Apart from that, the results of the analysis of student response questionnaires, which involved thirty-two students, showed that the learning media obtained an average that fell into the very practical category. The conclusion of this research is that the interactive PowerPoint learning media on the subject of statistics, the material focusing on single data, has been tested and proven to be very feasible and very practical.”